Fetal head–symphysis distance: a simple and reliable ultrasound index of fetal head station in labor. (6th March 2013) - Youssef, A.; Maroni, E.; Ragusa, A.; De Musso, F.; Salsi, G.; Iammarino, M. T.; Paccapelo, A.; Rizzo, N.; Pilu, G.; Ghi, T.
ABSTRACT Objectives To assess the reproducibility of measurement of a new sonographic index of fetal head station in labor, the fetal head–symphysis distance (HSD), using three‐dimensional ultrasound, and its correlation with digital assessment of fetal head descent and with the angle of progression (AoP). Methods Three‐dimensional (3D) ultrasound volumes were acquired from 47 nulliparous women in active labor following assessment of fetal head station with digital examination. The HSD (the distance between the lower edge of the pubic symphysis and the nearest point of the fetal skull) was measured independently by two operators in order to evaluate intra‐ and interobserver reproducibility. The correlation between HSD, AoP and fetal head station was evaluated using regression analysis. Using 3D tomographic ultrasound imaging (TUI), measurements of the HSD were obtained in different parasagittal planes to evaluate the influence of inaccurate alignment of the probe with the midline of the pelvis. Results Measurement of HSD showed high intraobserver (intraclass correlation coefficient (ICC) = 0.995; 95% CI, 0.991–0.997) and interobserver (ICC = 0.991; 95% CI, 0.984–0.995) reliability. In addition, a high correlation was demonstrated between mid‐sagittal and parasagittal HSD measurements. HSD showed significant negative correlation with both fetal head station and AoP. Conclusion Fetal HSD is a simple and reliable method for the assessment of fetal head descent in labor. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.